Protective Effect of Natrium Diethyldithiocarbamate Trihydrate (NDDCT) on Lead Induced Neurodegeneration in Rats - Kumar, Sudhir; Maurya, Harikesh; Sandeep, Sandeep; Sen, Saikat; Chakraborty, Raja (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim: Lead is a powerful metal which induced neurotoxicity through the degradation of neurons in the body. Various neuronal changes have shown correlation with the generation of free radicals and oxidative stress. The present study was carried out to evaluate the neuroprotective activity of Natrium diethyl dithiocarbamate trihydrate (NDDCT) on lead induced neurodegeneration in rat’s model. Methods: We have evaluated the neuroprotective activity of NDDCT using Morris Water maze, Elevated plus maze, Photoactometer and Hebb’s William maze models and also evaluated different biochemical parameters. Neurodegeneration was induced by administering lead acetate (1 mg/kg/day) for 35 days. Test drug NDDCT (5 mg/kg and 10 mg/kg) and standard drug donepezil were also administered concurrently in test and standard drug treated group. Results: NDDCT found to improve escape latency time (in Morris Water Maze), transfer latency time (in Elevated plus Maze), time to reach reward chamber (Hebb William’s Maze) and locomotor activity. The neuroprotective activity of NDDCT was confirmed by evaluation of in vivo antioxidant and estimation of other biochemical parameters. NDDCT found to improve the level of reduced glutathione, catalase, superoxide dismutase, sodium nitrate and reduced the level of serum lead, TNF-α, nitric oxide, acetylcholinesterase enzyme in the test group when compared with the disease control group. Histopathological evaluation of the brain also confirms the protective effect of NDDCT. Conclusion: These results suggest that NDDCT can be used as a preventive drug against lead-induced neurodegeneration, cholinergic dysfunctions and oxidative stress.
Keywords: Natrium diethyldithiocarbamate trihydrate (NDDCT); Neuroprotective; Biomarkers; Physical activity; Neurodegeneration; Cholinergic dysfunction